Indeks Ekologi Komunitas Tintinnid (Protozoa:Ciliophora) di Perairan Banggai, Sulawesi Tengah - Sugiyanto, Nenden Rose; Widianingsih, Widianingsih; Suryono, Chrisna Adhi; Hartati, Retno; Endrawati, Hadi (Universitas Diponegoro, 2024)
There are several groups of organisms in zooplankton, including ciliates (Filum Ciliophora). Ciliates that live in the sea belong to the suborder tintininna or also often referred to as tintinnids. This study aims to determine the type and abundance and analyze the ecological index of the tintinnid community in Banggai Waters, Central Sulawesi. This research was conducted at 35 stations on 1 – 14 September 2022 in the Banggai Waters, Central Sulawesi. The samples were taken by vertical method. The results showed that 9 families, 20 genera, and 35 tintinnid species were identified. The abundance of tintinnids in Banggai Waters has an average of 5763 cells/m3. Furthermore, the distribution pattern of total abundance at each station shows a clustered distribution pattern. The diversity of tintinnid abundance in Banggai Waters has an average of 2.15, classified as moderate. Tintinnid uniformity in Banggai Waters has an average of 0.63 classified as high. The dominance of tintinnids in Banggai Waters has an average of 0.17 classified as low category. The relationship between total abundance and diversity index shows a positive correlation. Meanwhile, the relationship between the abundance and evenness indices and the dominance indices shows a negative correlation. The study's results suggest that the condition of the tintinnid community in Banggai Waters is stable. Filum Ciliophora (Ciliata) termasuk dalam kelompok mikrozooplankton. Ciliata yang hidup di laut termasuk ke dalam subordo Tintininna atau juga sering disebut dengan tintinnid. Penelitian ini bertujuan untuk mengetahui jenis, kelimpahan, dan indeks ekologi dari komunitas tintinnid yang berada di Perairan Banggai, Sulawesi Tengah. Pengambilan sampel dilakukan pada tanggal 1- 14 September 2022 di Perairan Sulawesi Tengah. Sampel mikrozooplankton diambil secara vertikal pada 35 stasiun. Hasil penelitian menunjukkan bahwa ditemukan 9 famili, 20 genus, dan 35 spesies tintinnid yang teridentifikasi. Kelimpahan tintinnid di Perairan Banggai memiliki rata-rata sebesar 5763 sel/m3. Selanjutnya pola sebaran dari kelimpahan total di tiap stasiun menunjukkan pola sebaran mengelompok. Kenekaragaman Kelimpahan tintinnid di Perairan Banggai memiliki rata-rata sebesar 2,15 tergolong kategori sedang. Keseragaman tintinnid di Perairan Banggai memiliki rata-rata sebesar 0,63 tergolong kategori tinggi. . Dominansi tintinnid di Perairan Banggai memiliki rata-rata sebesar 0,17 tergolong kategori rendah. Hubungan anatara kelimpahan total dengan indek keanekaragaman menjukkan korelasi positif. Sedangkan hunbungan antrara kelimpahan dengan indek keseragman dan indek dominansi menjukkan adanya korelasi negatif. Berdasarkan hasil penelitian dapat disimpulkan bahwa kondisi komunitas tintinnid di Perairan Banggai termasuk stabil.